1998
DOI: 10.1111/j.1365-2672.1998.tb05286.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil: the environmental source of Escherichia coli and Enterococci in Guam's streams

Abstract: We have previously documented that faecal indicator bacteria (Escherichia coli, faecal coliform, enterococci) recommended by the U.S. Environmental Protection Agency (USEPA) to establish recreational water quality standards are naturally found in high concentrations in the surface and subsurface of soils in Hawaii. Rain, the source of all streams in Hawaii, washes the soil sources of faecal bacteria into all the streams of Hawaii, at concentrations which consistently exceed the USEPA recreational water quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
135
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 4 publications
9
135
3
1
Order By: Relevance
“…An adequate faecal indicator does not reproduce outside the animal host. E. coli and enterococci grow, survive and establish their populations in natural environments such as freshwater lakes and streams (Byappanahalli et al 2003;Power et al 2005), algal wrack (Olapade et al 2006;Whitman and Nevers 2003), beach sand (Byappanahalli, Whitman, Shively, Ting, et al 2006;Whitman et al 2005), soils and sediments (Anderson et al 2005;Byappanahalli and Fujioka 2004;Byappanahalli, Whitman, Shively, Sadowsky, et al 2006;Fujioka et al 1999;Ishii et al 2006;Solo-Gabriele et al 2000;Whitman et al 2005), and plant cavities (Whitman et al 2005).…”
Section: Pollution Due To Sewage In Urban Areasmentioning
confidence: 99%
“…An adequate faecal indicator does not reproduce outside the animal host. E. coli and enterococci grow, survive and establish their populations in natural environments such as freshwater lakes and streams (Byappanahalli et al 2003;Power et al 2005), algal wrack (Olapade et al 2006;Whitman and Nevers 2003), beach sand (Byappanahalli, Whitman, Shively, Ting, et al 2006;Whitman et al 2005), soils and sediments (Anderson et al 2005;Byappanahalli and Fujioka 2004;Byappanahalli, Whitman, Shively, Sadowsky, et al 2006;Fujioka et al 1999;Ishii et al 2006;Solo-Gabriele et al 2000;Whitman et al 2005), and plant cavities (Whitman et al 2005).…”
Section: Pollution Due To Sewage In Urban Areasmentioning
confidence: 99%
“…Studies conducted in Hawaii and Guam (Fujioka, 1988;Fujioka and Roll, 1997;Fujioka et al, 1999), and in Puerto Rico (Toranzos and Marcos, 2000) have shown that in the absence of any known sources of human/animal waste, enterococci and E. coli are consistently present and recovered in high concentrations in the subtropical environment. Specifically in South Florida, river bank soils and beach sands have been implicated as the source of indicator microbes to the water column (Desmarais et al, 2002;Rogerson et al, 2003;Shibata et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In many watersheds, wildlife such as geese and deer are a significant source of E. coli [5][6][7]. E. coli is also associated with point-source discharges of human wastes such as those which occur at wastewater treatment plants [8]. The concentration of fecal coliforms in treatment plant effluent depends on flow, treatment type, and the target bacterial population [9,10].…”
Section: Introductionmentioning
confidence: 99%